Care Neonatal Normal Primary Clinic Arrabih In Pekanbaru 2018: Care Neonatal Normal Primary Clinic Arrabih In Pekanbaru 2018 - Selvi July Yanti (Institute Of Computer Science (IOCS), 2020)
Newborns, neonates Also called, are individuals who are growing and have recently undergone birth trauma and should be Able to Adjust Themselves from intrauterine life to etraurerine life (the Goddess, 2012) .Based on the Indonesian Demographic health Reached 32 per 1000 live births ( MOH, 2012) .from the Data Obtained in Promkes & Kesga Field and Profile of DHO / Provence of Riau Province in 2014, the live birth rate per month Reaches 10,000 births newborns should get more standardized examinations more Often, high infant, ortality is due to neonatal complications of hypothermia, asphyxia and infection. This case study report aims to provide complete and continuous nursing care of the normal newborn 0-48hours to maintain the airway and breathing support, maintain warmth and Prevent hyporthermia, Prevent infection and identify actual or potential concerns that require attention, This case study was conducted at the Clinic Primary Al-Rabih. It is recommended that maintain and improve existing Midwives Midwifery care, especially normal newborn.In Midwifery care in order to avoid complications due to improper handling of newborns.So that willhelp the government program Neotanus reduce the death rate.